Emotional distress in haemophilia: Factors associated with the presence of anxiety and depression symptoms among adults. Issue 5 (13th July 2018) - Pinto, P. R.; Paredes, A. C.; Moreira, P.; Fernandes, S.; Lopes, M.; Carvalho, M.; Almeida, A.
Abstract : Introduction: Haemophilia is related to several clinical and psychosocial challenges that have been associated with increased emotional distress. These may impact on disease adjustment and health outcomes, reinforcing the attention given to psychosocial health of people with haemophilia (PWH), in the scope of optimal comprehensive care. Aim: To identify potentially modifiable factors associated with the presence of anxiety and depression symptoms among adult PWH. Methods: This was a cross‐sectional observational study examining socio‐demographic, clinical and psychosocial variables among 102 patients with haemophilia A or B who participated on a mail survey of haemophilia in Portugal. Results: People with haemophilia revealing higher anxiety and depression symptoms were more likely to have had, in the previous year, more urgent hospital visits due to haemophilia, more bleeding episodes, more affected joints and pain, as well as worst levels of perceived functionality and quality of life. After controlling for demographic (age and education) and clinical (haemophilia severity and joint deterioration) variables in multivariate hierarchical logistic regression analyses, professional status (OR = 4.646, P  =   .004; OR = 3.333, P  =   .029) and pain interference (OR = 1.397, P  =   .011; OR   =   .1.347, P  =   .037) were significantly associated with both anxiety and depression symptoms. Additionally, physical activity (OR = 0.302, P  =   .024) and the perception of consequences underlying haemophilia (OR = 1.600, P  =   .012) also emerged as key factors significantly associated with depression symptoms. Conclusion: Current findings increased knowledge on factors associated with anxiety and depression among PWH. These highlight potential intervention targets, which are amenable to change through evidence‐based tailored interventions aiming to decrease emotional distress, promote well‐being and improving haemophilia‐related health outcomes among these patients.